2007
DOI: 10.1002/macp.200600440
|View full text |Cite
|
Sign up to set email alerts
|

2,5‐Substituted PPV‐Derivatives with Different Polarities: The Effect of Side Chain Polarity on Solubility, Optical and Electronic Properties

Abstract: Three 2,5‐substituted polar PPV derivatives have been prepared using the sulfinyl precursor route and compared to the apolar MDMO‐PPV. All polymers were obtained in excellent yield and with improved purity as compared to other methods. The influence of the polarity of the side chains, i.e. oligo(oxyethylene) and alkyl substituents, on the optical and electronic properties were investigated. In thin films, the oligo(oxyethylene) substituents do not significantly alter the optical properties of the conjugated ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…The synthesis and characterization have been previously reported. 13 Furthermore, previous studies using impedance measurements have shown the relative permittivity of the material to be equal to 4. 14 The chemical structure of phenyl-C 61 butyric acid 2-ethylhexyl ester ͑PCB-EH͒, which is the acceptor used here, is also shown in Fig.…”
Section: Theorymentioning
confidence: 99%
“…The synthesis and characterization have been previously reported. 13 Furthermore, previous studies using impedance measurements have shown the relative permittivity of the material to be equal to 4. 14 The chemical structure of phenyl-C 61 butyric acid 2-ethylhexyl ester ͑PCB-EH͒, which is the acceptor used here, is also shown in Fig.…”
Section: Theorymentioning
confidence: 99%
“…Examples are the Wessling, [26] sulfinyl, [27][28][29][30][31][32][33][34] sulfonyl, [35,36] xanthate, [37][38][39] dithiocarbamate, [40] Gilch, Heck, [69][70][71][72][73] Suzuki, [74,75] McMurry, [76] ring-opening metathesis, [77,78] acyclic diene metathesis, [79][80][81] Wittig, [82][83][84] Horner-Emmons, [85] Knoevenagel, [86] chemical vapor deposition, [87][88][89][90][91] and electropolymerization [92] methods. By assessing the pros and cons of all these approaches, the Gilch route stands out as one of the most powerful, versatile, and economically efficient approaches: simply by the treatment of a,a 0 -dihalogenated p-xylene derivatives 1 with potassium tert-butoxide (KO t Bu), high-molecular-weight PPVs 2 can be obtained in good to excellent yields (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that the optical properties of CPs are governed by the polarity of the polymer, conformational changes in the backbone, the polarity of the solvent, intramolecular dynamics, and interchain interactions [ 55 , 56 ]. A change in the conformation of the polymer chain is dictated by different variables, among which solvent and temperature are prominent.…”
Section: Resultsmentioning
confidence: 99%
“…Fluorescence intensity increased for both of the polymers as pH values increased, without shifting of emission maxima peaks ( Figure 3 c,d). A slight blue shift is observed for PDTriG with decreasing acidity, at pH 6 and below, due to aggregation of amphiphilic CPs as they become protonated [ 56 ]. It was, however, observed that the fluorescence intensity of PDTriG decreased in time at pH 13 and at pH 6 and lower.…”
Section: Resultsmentioning
confidence: 99%